Nothing ventured, nothing gained : rewiring the DNA in banking - Manson, Alex (Emerald Publishing Limited, 2025)
Nothing Ventured, Nothing Gained: Rewiring the DNA in Banking offers a behind-the-scenes look at how SC Ventures, Standard Chartered Banks, Standard Chartered Bank's innovation, fintech, investment and ventures arm, embraced disruption to thrive in an era of rapid change. In today's evolving financial landscape, business leaders know that innovation is key to sustainability, yet many hesitate to embrace the full scope of transformation. Written by the CEO, Alex Manson, and thought leaders within the bank, Nothing Ventured, Nothing Gained reveals how SC Ventures overcame this challenge by fostering innovation, investing in disruptive financial technology, and exploring alternative business models. This candid account showcases the rise of SC Ventures, a leader in the fintech and venture capital industries. Essential reading for anyone interested in the future of banking and the forces reshaping the industry.